2018
DOI: 10.1016/j.jaad.2017.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial drug toxicities in patients with cutaneous lupus and dermatomyositis: A retrospective cohort study

Abstract: With the exception of retinopathy, which was not seen with Q, the risks for other toxicities associated with Q monotherapy or combination treatment were not significantly different from those with HCQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
2
28
0
3
Order By: Relevance
“…However, QC is not available in most European countries because of reports of aplastic anemia. Of note, in the study of Mittal et al, no severe anemia or retinopathy was observed with QC [62].…”
Section: Switch Of Am Agent or Addition Of Qcmentioning
confidence: 78%
“…However, QC is not available in most European countries because of reports of aplastic anemia. Of note, in the study of Mittal et al, no severe anemia or retinopathy was observed with QC [62].…”
Section: Switch Of Am Agent or Addition Of Qcmentioning
confidence: 78%
“…glucocorticoids may not be practical, oral antimalarials are also considered first‐line therapy. HCQ is most often the first used in the US, as it is effective with a more favorable side effect profile than chloroquine (16). If the disease does not respond to HCQ, quinacrine can be added.…”
Section: Clinical Challengementioning
confidence: 99%
“…Mittal et al recently reported a 11% rate of antimalarialinduced cutaneous hypersensitivity eruptions in a combined dermatology clinic-ascertained cohort of 532 cutaneous LE and dermatomyositis patients (30% of this patient cohort had dermatomyositis) (28). In addition, Chasset et al concurrently reported a 3-12% rate of antimalarialsinduced cutaneous hypersensitivity reactions in their study group of 64 French antimalarial-treated cutaneous LE patients (29).…”
mentioning
confidence: 99%